Knowledge, Attitudes, and Practices of 50 Patients with Surgically Treated Cystic Echinococcosis from Basrah Province, Iraq - Mohanad Faris Abdulhameed; Ian Duncan Robertson; Suzan Ali Al-Azizz; Ihab Habib (Springer, 2018)
Cystic echinococcosis (CE) is recognised worldwide as a neglected disease of public health concern, particularly in low- and middle-income countries. The objectives of this study were to describe, using a questionnaire survey, the characteristics, attitudes, knowledge, and practices of patients with CE from Basrah Province, Iraq. We interviewed 50 patients, 31 female and 19 male, of whom, 74% originated from rural areas. Approximately half (48%) of the participants reported slaughtering livestock at home for their families' consumption; 78% indicated the presence of a large number of stray dogs roaming freely about their village; 86% reported that they never boiled water prior to drinking it; and 26% reported not washing vegetables prior to eating them. Although a large proportion of the participants (72%) had heard of hydatid disease prior to becoming ill, over half (57%) were not aware how the disease was transmitted from animals to humans. This study highlighted a gap in health education efforts regarding CE in Southern Iraq, with a lack of counselling of patients on how to prevent reinfection. An intensive control programme should be implemented and founded on health education to reduce CE disease in Basrah.